MANAJEMEN KONFLIK UNTUK MENCIPTAKAN KOMUNIKASI YANG EFEKTIF (Studi Kasus Di Departemen Purchasing PT. Sumi Rubber Indonesia) - Anwar, Choerul (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2015)
AbstractBad behavior committed by an employee in an organization will hinder communication amongits members. Bad behavior that often occurs at a company is blackmail, bribery, bullying, cheating,dishonesty, intimidation, invasion of privacy, sexual harassment, threats, theft, discrimination,misinformation. In the Purchasing Department of Sumi Rubber company there are a variety of badbehaviour that were found including the crime of aggresion, deceit, licentiousness, sabotage and theft.Communication means providing information and distributing to the members of the organization, ifthe distribution is hampered because of the bad behavior committed by a person or one of the employeesof the communication that exists becomes ineffective. In the long term ineffective communicationswill result in the emergence of misunderstanding interpretation giving rise to prejudice and ultimatelylead to internal conflicts within the company or organization. Role management is urgently neededto resolve the conflict because of the impact of impact of the conflict will impact on the performanceand effectiveness of the work in the company especially in Sumi Rubber company